High-temperature episyenites from late-Variscan Sàrrabus pluton (SE Sardinia, Italy) - F. Secchi; S. Naitza; A.M. Conte; G. Oggiano; M. Casalini; M. Kohút; T. Giovanardi (Lithos, 2026)

Far from the coast: organohalogen bioaccumulation in spinner dolphins from the Southwestern Atlantic - Caroline A.C. Corrêa; Bárbara M.R. Manhães; Nara Oliveira-Ferreira; Elitieri B. Santos-Neto; Eduardo R. Secchi; Juliana C. Di Tullio; Rodrigo C. Genoves; Haydée A. Cunha; Tatiana L. Bisi; Alexandre F. Azevedo; José Lailson-Brito (Marine Pollution Bulletin, 2026)

Contrasting adaptive strategies of Quercus robur and Q. rubra to severe drought driven by phosphorus supply - Rolando M.; Ganugi P.; Secchi F.; Celi L. (Plant and Soil, 2026)
Background and Aims Plant resilience to drought is strongly modulated by nutrient availability, which triggers complex physiological and metabolic reprogramming. In European forests, native species with high resource demands may be disadvantaged under abiotic stress compared to more efficient alien species. This study investigates how drought and phosphorous (P) availability affect the responses of Quercus robur (EO) and Quercus rubra (RO), focusing on root metabolism and nutrient allocation between leaves and roots. Methods A greenhouse mesocosm experiment was conducted with EO and RO subjected to two water regimes (well-watered and drought) and two P levels (− P and + P). Stem water potential, biomass, elemental composition, FTIR spectra, and root metabolomic profiles (UHPLC/QTOF-MS) were analyzed. Univariate and multivariate statistics were used to evaluate treatment effects. Results EO showed greater responsiveness to P, with increased root biomass and limited metabolic suppression during drought conditions. RO displayed a more stable biomass and elemental profile, but its metabolism was more strongly repressed under drought with P input. Under P deficiency, RO accumulated phenylpropanoids and alkaloids, indicating adaptation to low-resource stress. Conclusions EO exhibits higher metabolic plasticity and benefits from P supply under drought, while RO adopts a conservative strategy suited to nutrient-poor environments. These contrasting responses suggest that P availability may shift the competitive balance between native and alien oak species under climate-induced drought, favoring EO under P-rich conditions and RO under P-limited conditions.

Range-wide monitoring reveals demographic vulnerability in Lahille's bottlenose dolphins - Fábio G. Daura-Jorge; Paula Laporta; Ignacio B. Moreno; Paulo H. Ott; Paulo A.C. Flores; Pedro Volkmer de Castilho; André S. Barreto; Rodrigo Cezar Genoves; Carolina Bezamat; Alexandre M.S. Machado; Eduardo R. Secchi; Silvina Botta; et al. (Biological Conservation, 2026)

Grapevine adopts different strategies in response to drying regimes. Procrastinator or escaper? - C. Morabito; J. Orozco; A. Asteggiano; C. Medana; A. Schubert; M.A. Zwieniecki; F. Secchi (Journal of Plant Physiology, 2025)

The interplay between drought and phosphorus scarcity shapes resilience to stress in Quercus spp. by modulating metabolomic profiles - M. Rolando; P. Ganugi; L Zhang; F Secchi; L Lucini; L Celi (Plant and Soil, 2025)
Background and aims Plant resilience to drought conditions is modulated by physiological and metabolic responses, including the accumulation of antioxidant metabolites. These mechanisms can be in influenced by nutrient availability, especially phosphorus (P). In European mixed forests, native species with high resource demands often compete with more efficient alien species, whose advantages under abiotic stress can enhance their invasiveness. This study investigates how drought and P availability affect the resilience of two Quercus species differing in stress tolerance and resource use efficiency. Methods We conducted a mesocosm experiment in which the native Q. robur (English oak, EO) and alien Q. rubra (Red oak, RO) were grown under well-watered or drought conditions, with or without P supplementation. Leaf gas exchange and stem water potential were measured, leaves and soil were chemically characterized, and metabolite biosynthesis was investigated using an omics approach. Results During drought, the metabolism of P-supplied EO shifted toward the accumulation of phenylpropanoids, flavonoids, saikosaponins, mannitol, and long-chain fatty acids, which are compounds known for their antioxidant, osmoprotectant, and membrane-stabilizing functions. Conversely, RO plants displayed a more conservative metabolic profile, with limited changes in response to P supply. Under P deficiency, RO accumulated secondary metabolites such as phenylpropanoids and alkaloids, highlighting its ability to withstand combined nutrient and water stress. Conclusions Our results reveal contrasting adaptive strategies: EO is more susceptible to drought stress, but its resilience can be modulated by P availability, whereas RO maintains more stable physiological and metabolic functions, consistent with higher nutrient-use efficiency.

Persistent organic pollutants and fatty acids in humpback whales: Antarctic and Chilean feeding and Brazilian breeding sites - Cristian T. Timoszczuk; Satie Taniguchi; Josilene da Silva; Lucas Costa Pereira; Luciano Dalla Rosa; Eduardo R. Secchi; Javier Negrete; João Carlos Gomes Borges; Salvatore Siciliano; Paula Baldassin; Jorge Acevedo; Anelio Aguayo-Lobo; et al. (Science of The Total Environment, 2025)

Modeling and theorizing with agent-based sustainable development - D. Secchi; V. Grimm; D.B. Herath; F. Homberg (Environmental Modelling & Software, 2024)

The deep dive of organohalogen compounds: Bioaccumulation in the top predators of mesopelagic trophic webs, pygmy and dwarf sperm whales, from the Southwestern Atlantic ocean - Nara de Oliveira-Ferreira; Elitieri B. Santos-Neto; Bárbara M.R. Manhães; Vitor L. Carvalho; Letícia Gonçalves; Pedro V. de Castilho; Eduardo R. Secchi; Silvina Botta; Milton C.C. Marcondes; Adriana C. Colosio; Marta J. Cremer; Haydée A. Cunha; et al. (Chemosphere, 2023)

An additional threat to populations predicted to collapse: Organobromine compounds of natural and anthropogenic sources in rough-toothed dolphins from the Southwestern Atlantic Ocean - Nara de Oliveira-Ferreira; Elitieri B. Santos-Neto; Bárbara M.R. Manhães; Camila Domit; Eduardo R. Secchi; Silvina Botta; Haydée A. Cunha; Alexandre F. Azevedo; Tatiana L. Bisi; José Lailson-Brito (Chemosphere, 2023)

Syntectonic magmatism and reactivation of collisional structures during late-Variscan shearing (SW Sardinia, Italy) - F. Secchi; L. Casini; F. Cifelli; S. Naitza; E. Carta; G. Oggiano (International Journal of Earth Sciences, 2022)
The Arbus igneous complex (SW Sardinia, Italy) represents a good example of a short time lived post-collisional composite pluton emplaced at shallow crustal level in the external zone of the Variscan chain. The pluton almost consists of granodiorite and leucogranite rock- suites emplaced at 304 ± 1 Ma within a main NW trending thrust separating the metamorphic wedge from the fold and thrust belt foreland. The pluton emplaced into a dilatational step over connecting two NW–SE dextral shear zones which belongs to a regional network of post-collisional strike-slip structures marking the transition from collision to post-collisional extension. The microstructure observed for quartz and K-feldspar confirms the lack of significant post-emplacement deformation, indicating only limited high-temperature sub-solidus recrystallization. Anisotropy of magnetic susceptivity data and field-structural analysis have been carried out to reconstruct the geometry of the pluton and the trajectories of magmatic flow in relation to regional deformation structures. Overall, the magmatic and the magnetic fabrics are broadly discordant with the metamorphic foliation of the country rocks, defining an EW trending elliptical asymmetric sill rooted in the SW quadrant. The reconstructed architecture combined to petrologic observation indicates that accretion of the pluton involved injection of multiple dykes through a sub-vertical feeder zone, combined to lateral flow of the roof controlled by inherited collisional structure. The duration of magmatic activity and the cooling history of the contact metamorphic aureole have been evaluated through a suite of 2D thermal models. All these observations, together with the available geochronological constraints are suggestive of very rapid construction of the pluton. The proposed emplacement model is fully consistent with the regional phase of strike-slip tectonics and widespread magmatism accommodating the large rotation of the Corsica-Sardinia block during the Carboniferous-Permian transition.

Seasonal population parameters reveal sex‐related dynamics of common bottlenose dolphins in open waters of the southwestern Gulf of Mexico - Jaime Bolaños‐Jiménez; Eduardo Morteo; Pedro F. Fruet; Christian A. Delfín‐Alfonso; Eduardo R. Secchi; Javier Bello‐Pineda (Marine Mammal Science, 2022)
In coastal populations of the common bottlenose dolphin, resident females are usually more abundant and have more restricted home ranges than males. Here, we studied sex‐specific population dynamics of bottlenose dolphins off the Alvarado Lagoon System, southwestern Gulf of Mexico. We used standard photo‐identification and capture‐mark‐recapture methods to determine population parameters under the superpopulation approach. Seasonal survival fluctuated around 0.96 (range: 0.80–1.00) and was equal for the sexes; recruitment of putative females (PF) and males (PM) was low, asynchronous, and reached 0.14 (range: 0.04–0.10) and 0.09 (range: 0.09–0.09), respectively, indicating high residency. PF abundance ranged from 60, 95% CI [48, 74] in the northern winds' season of 2008 to a low of 38, 95% CI [31, 47] in the dry season of 2010. PM abundance ranged from a high of 14, 95% CI [12, 16] in the northern winds' season of 2008 to a low of 9, 95% CI [7, 11] in the dry season of 2010. A regression analysis showed significant autocorrelation, and a pattern in the residuals of abundance, indicating no trends as well as temporal fluctuations that suggest a possible carrying capacity effect. Accordingly, high site fidelity, restricted ranging patterns, and low sporadic recruitment from the superpopulation are likely driving population parameters for this population.

Population Dynamics Reveal a Core Community of the Common Bottlenose Dolphin (Tursiops truncatus) in Open Waters of the South-Western Gulf of Mexico - Jaime Bolaños-Jiménez; Eduardo Morteo; Christian A. Delfín-Alfonso; Pedro F. Fruet; Eduardo R. Secchi; Javier Bello-Pineda (Frontiers in Marine Science, 2021)
The presence of transient and temporary individuals in capture-mark-recapture studies may violate the assumption on equal catchability, and thus yield biased estimates. We investigated the effects of residency patterns on population parameters of bottlenose dolphins inhabiting the coastal waters off the Alvarado Lagoon System (ALS), Veracruz, Mexico. We hypothesized that this population is open but there exists a “core community” that behaves as a closed population. Between 2006 and 2010, we conducted 75 photo-identification surveys and recorded 263 dolphin group encounters, in which 231 dolphins were identified. Individuals present during only one season, classified as transients ( n = 85), were excluded from the study, and a standardized residency index (IH 4 ) was computed for each dolphin that remained in the sample ( n = 146). We used the K-means clustering method to split the sample into groups based on individual (seasonal, annual) IH 4 values. These clusters were named as regular residents (RR, n = 55), occasional residents (OR, n = 45), and occasional visitors (OV, n = 46). The cumulative frequency of newly identified individuals displayed an asymptotic trend for the whole sample and all clusters, indicating that most of the individuals present in the study area during the study period were identified. The assumption of demographic closure was tested to define the core community, and was rejected for the whole sample and the OV cluster ( p < 0.001 in both cases), indicating that the population is open. The closure assumption was not rejected for RR and OR clusters (χ 2 = 6.88, DF = 13, p = 0.91, and χ 2 = 17.8, DF = 16, p = 0.33, respectively), indicating that these clusters were demographically closed over the 5-year period. Thus, we defined this aggregation of individuals as the “core community”. The closed population model M th indicated that the total abundance of this core community was 123 individuals (95% CI: 114–133). Our results provide quantitative evidence of the existence of a core community in open waters of the Gulf of Mexico, and points toward residency pattern as a main driver of population dynamics. These results highlight the importance of considering residency patterns when dealing with heterogeneity in the sample of a highly mobile species.

Dynamics and Viability of a Small, Estuarine-Resident Population of Lahille’s Bottlenose Dolphins From Southern Brazil - Pedro F. Fruet; Luciana M. Möller; Eduardo R. Secchi (Frontiers in Marine Science, 2021)
Identifying threatened populations and quantifying their vulnerability is crucial for establishing priorities for conservation and providing robust information for decision-making. Lahille’s bottlenose dolphins have been long subjected to by-catch mortality in gillnet fisheries in coastal waters of southern Brazil, particularly in the Patos Lagoon estuary (PLE) and adjacent coastal waters, where dolphins from three populations (or Management Units) show overlapping home ranges. In this study we used a stage-classified matrix population model to conduct a demographic analysis of the PLE’s population with life-history data estimated through an 8 years mark-recapture study. A population viability analysis (PVA) was used to run a series of simulations where the risk was assessed under different by-catch scenarios, taking into account the effects of parameter uncertainty and stochasticity in the projections. In the absence of by-catch, we estimated that this dolphin population would growth at a rate of about 3% annually (95% CI: 1.2–5.8%). Under current by-catch rates, prognoses indicated high probabilities of viability over the next 60 years. These optimistic prognoses appear to be associated with the high survival of adult females. However, the eventual removal of very few mature females (one every year or two) would result in a prominent likelihood of decline from its current abundance at all pre-specified levels. The viability of the population would be substantially improved if the survival of juveniles/sub-adults could be increased. This may be achieved through the recently implemented dolphin protection area, which prohibits gillnet fisheries in the core area of this population. If the protection area reduces the entanglement rates of the most impacted life-stages (i.e., juvenile/sub-adult dolphins), there would be a substantial chance of the PLE’s dolphin population increasing above 20% of its current size, which is here proposed as conservation goal. If met, this goal has the potential to promote habitat quality, increase genetic diversity and connectivity with adjacent populations, enhancing the ability of bottlenose dolphins in southern Brazil to cope with environmental change and potential disease outbreaks.

Age structure of strandings and growth of Lahille's bottlenose dolphin ( Tursiops truncatus gephyreus ) - Rihel Venuto; Silvina Botta; André S. Barreto; Eduardo R. Secchi; Pedro F. Fruet (Marine Mammal Science, 2020)
This study describes the age structure and sex‐specific growth patterns of Lahille's bottlenose dolphins ( Tursiops truncatus gephyreus ), a subspecies endemic to the Southwest Atlantic Ocean (SWAO). The ages of 120 animals collected in southern Brazil between 1976 and 2017 were determined. We found high frequencies of young animals, mostly males, with no sex bias among adults. A temporal change in the age structure of strandings was observed, and we conclude it is a consequence of increased bycatch rates of young dolphins after 2000. The oldest male and female were 27 and 44 years old, respectively, suggesting that females live longer than males in southern Brazil. Growth curve analysis using Gompertz and Laird‐Gompertz growth models estimated asymptotic lengths of 316.5 cm for females and 351.6 cm for males, (reached around 13 and 18 years old, respectively), supporting sexual size dimorphism for the subspecies. A second growth pulse was identified for males. Our work highlights the benefit of long‐term studies and contributes valuable information toward understanding the life history of Lahille's bottlenose dolphin. It will serve as baseline for future studies that seek to understand mortality patterns of bottlenose dolphins elsewhere and the effects of anthropogenic actions on the survival of these animals.

Diverse groups of fungi are associated with plastics in the surface waters of the Western South Atlantic and the Antarctic Peninsula - Ana L. d. F. Lacerda; Maíra C. Proietti; Eduardo R. Secchi; Joe D. Taylor (Molecular Ecology, 2020)
Marine plastic pollution has a range of negative impacts for biota and the colonization of plastics in the marine environment by microorganisms may have significant ecological impacts. However, data on epiplastic organisms, particularly fungi, is still lacking for many ocean regions. To evaluate plastic associated fungi and their geographic distribution, we characterised plastics sampled from surface waters of the western South Atlantic (WSA) and Antarctic Peninsula (AP), using DNA metabarcoding of three molecular markers (ITS2, 18S rRNA V4 and V9 regions). Numerous taxa from eight fungal phyla and a total of 64 orders were detected, including groups that had not yet been described associated with plastics. There was a varied phylogenetic assemblage of predominantly known saprotrophic taxa within the Ascomycota and Basidiomycota. We found a range of marine cosmopolitan genera present on plastics in both locations, i.e., Aspergillus, Cladosporium , Wallemia and a number of taxa unique to each region, as well as a high variation of taxa such as Chytridiomycota and Aphelidomycota between locations. Within these basal fungal groups we identified a number of phylogenetically novel taxa. This is the first description of fungi from the Plastisphere within the Southern Hemisphere, and highlights the need to further investigate the potential impacts of plastic associated fungi on other organisms and marine ecosystems.

Distribution, habitat use, and abundance of the endangered franciscana in southeastern and southern Brazil - Federico Sucunza; Daniel Danilewicz; Artur Andriolo; Alexandre F. Azevedo; Eduardo R. Secchi; Alexandre N. Zerbini (Marine Mammal Science, 2020)
The franciscana ( Pontoporia blainvillei ) is endemic to coastal waters from Brazil to Argentina. The species is regarded as one of the most threatened cetaceans in South America due to high bycatch levels. Four management units (FMAs) were defined throughout the species’ range. FMA II includes states along southeastern and southern Brazil, and represents one of the least known units. Recently, genetic analysis proposed that FMA II comprises two distinct populations and its range should be divided into FMA IIa and IIb. In December 2008 and January 2009 aerial surveys were conducted to assess the distribution and to estimate abundance of franciscanas off FMA II. A total of 54 groups were seen (average group size = 2.76, SE = 0.17) in shallow (mean depth = 7.15 m, SE = 7.08) coastal habitats (average distance from the shore = 6.48 km, SE = 6.28). Abundance corrected for perception and availability bias was estimated at 6,827 ( CV = 0.26) franciscanas in FMA II, and at 1,915 ( CV = 0.32) and 4,353 ( CV = 0.24) franciscanas in FMA IIa and FMA IIb, respectively. This study indicates that, at least during the summer, franciscanas aggregate in shallow coastal habitats. Current estimates of incidental mortality in FMA II correspond to 4.4%–7.3% of the estimated stock size, suggesting high, likely unsustainable bycatch.

Fine-scale genetic structure in Lahille’s bottlenose dolphins (Tursiops truncatus gephyreus) is associated with social structure and feeding ecology - Rodrigo Cezar Genoves; Pedro F. Fruet; Silvina Botta; Luciano B. Beheregaray; Luciana M. Möller; Eduardo R. Secchi (Marine Biology, 2020)

Cetacean distribution in relation to environmental parameters between Drake Passage and northern Antarctic Peninsula - Manuela Bassoi; Jorge Acevedo; Eduardo R. Secchi; Anelio Aguayo-Lobo; Luciano Dalla Rosa; Daniel Torres; Marcos C. O. Santos; Alexandre F. Azevedo (Polar Biology, 2020)

Using mark-recapture and stranding data to estimate reproductive traits in female bottlenose dolphins (Tursiops truncatus) of the Southwestern Atlantic Ocean - Pedro F. Fruet; Rodrigo Cezar Genoves; Luciana M. Möller; Silvina Botta; Eduardo R. Secchi (Marine Biology, 2015)

Dietary consistency of male South American sea lions (Otaria flavescens) in southern Brazil during three decades inferred from stable isotope analysis - L. Zenteno; E. Crespo; D. Vales; L. Silva; F. Saporiti; L. R. Oliveira; E. R. Secchi; M. Drago; A. Aguilar; L. Cardona (Marine Biology, 2015)

Remarkably low genetic diversity and strong population structure in common bottlenose dolphins (Tursiops truncatus) from coastal waters of the Southwestern Atlantic Ocean - Pedro F. Fruet; Eduardo R. Secchi; Fábio Daura-Jorge; Els Vermeulen; Paulo A. C. Flores; Paulo César Simões-Lopes; Rodrigo Cézar Genoves; Paula Laporta; Juliana C. Di Tullio; Thales Renato O. Freitas; Luciano Dalla Rosa; Victor Hugo Valiati; et al. (Conservation Genetics, 2014)

Growth hormone secretion in relation to plasma lactate and glucose concentrations during a maximal treadmill exercise test in horses - V. Borromeo; F. Ferrucci; E. Zucca; A. Berrini; C. Secchi (Veterinary Research Communications, 2008)

Monoclonal Antibody Capture Fluorometric Enzyme-Linked Immunosorbent Assay for Detection of Equine Growth Hormone in Plasma - V. Borromeo; F. Abbate; A. Berrini; A. Bartolone; C. Secchi (Veterinary Research Communications, 2005)